Omnibuslaw, Theory and Practice in the Field of Tourism Investment - Bendesa Gede Mas Indriyanigraha Arjaya; Anak Agung Ngurah Alit Wiraputra (Warmadewa Press, 2025)
Execution is the implementation of a court decision that has permanent legal force (in krach van gwijsde) which is carried out by force against the losing party in a case who does not want to comply with the implementation of the court decision. As with the